Determinação voltamétrica de catequina por eletrodo de carbono impresso modificado com nanotubo de carbono funcionalizado - SILVA, Ana Luisa (2014)
The catechin compound is a phenolic that has a great oxidant action,it is found in a different kinds of food such as wine, juice and tea, its application to inhibit ultraviolet radiation, reduces the level of cholesterol, among others. Currently, techniques are used for determining catechin as a gas chromatography, high performance liquid chromatography, although the electrochemical detection method is a promising yet, because it is less cumbersome and can distinguish between the oxidized and the reduced form of catechin. A growing number of studies has shown the necessity for a hurry procedure to availible the content of catechin and electrochemical techniques have been successfully employed. The research activities carried out in this study were the characterization and optimization of the parameters used for the determination of catechin in a printed carbon electrode modified with functionalized carbon nanotube by means of cyclic voltammetry technique and application in the quantification of this analyte in a sample of black tea. The best results were obtained at a concentration of 1x10-3 mol L-1 through catechin phosphate buffer 0.1 mol L-1 pH 7.0 using a potential sweep rate of 0.05 V s-1. From these conditions an analytical curve was obtained by linear response over the concentration range of catechin between 2.0 × 107 to 1.68 × 10-5 mol L-1, as limits of detection and quantification of 9.2 x10-8 and 3.0x10-7 mol L-1, respectively. The oxidation of catechin showed a peak located around 0.15 V vs. Ag / AgCl potential being near the peak shown in the literature.